2017
DOI: 10.1097/lbr.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Use of Single-Use Disposable Bronchoscope in the ICU in a Tertiary Referral Center of Singapore

Abstract: SB is equivalent in performance to CB in ICU. In addition, the SB may confer clinical, economic, and logistical advantages over the CB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Furthermore, Marshall et al also highlighted that less manpower is required to perform a successful intubation with aScope™. 56 This is also observed in our experience with Isiris α™ to remove ureteric stents. Another study by Tvede et al however, have shown that it is more expensive to use aScope™ for intubation compared to reusable optical scopes.…”
Section: Cost Analysissupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, Marshall et al also highlighted that less manpower is required to perform a successful intubation with aScope™. 56 This is also observed in our experience with Isiris α™ to remove ureteric stents. Another study by Tvede et al however, have shown that it is more expensive to use aScope™ for intubation compared to reusable optical scopes.…”
Section: Cost Analysissupporting
confidence: 62%
“…This article is distributed under the terms of the Creative Commons Attribution-Non Commercial 4.0 International License. ©2018 Phan et al Perbet et al, 55 Marshall et al, 56 have shown that the cost of using single-use, disposable aScope™ are comparable to traditional reusable optical scope. Furthermore, Marshall et al also highlighted that less manpower is required to perform a successful intubation with aScope™.…”
Section: Cost Analysismentioning
confidence: 99%
“…There may also be additional advantages in using disposable equipment, which may also have direct or indirect cost implications, such as the elimination of bronchoscope cross-infections and immediate availability in an emergency situation [ 9 , 32 , 33 ]. A recent article by Terjesen et al estimated additional costs associated with treatment of bronchoscope cross-infections to be $US203 per procedure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The costs of the differences in time required to complete the procedure and number of personnel assisting per procedure have not been included in the study. The delivery and preparation of ancillary equipment to facilitate a reusable bronchoscopy have been shown to delay the start time of the procedure when compared with using single-use bronchoscopes [ 32 ]. In contrast, the sensitivity analyses demonstrated scenarios where reusable bronchoscopes had the cost advantage; for example, when repair cost and repair ratio were below $US3530 and 3.7%, respectively, in combination with acquisition and reprocessing costs equal to $US150 per use or below.…”
Section: Discussionmentioning
confidence: 99%
“…With this important new information, a single documented case of true infection could instantaneously change standard practice to require the use of either a sterilized or a disposable bronchoscope. 18 The former proposal is time consuming and impractical for a busy bronchoscopy practice, whereas the latter needs to be established as both clinically and cost-effective. Patient safety is paramount; therefore, it is critical that if HLD remains the standard of care and is sufficient, it must done properly.…”
mentioning
confidence: 99%